Morbidity, mortality and temporal trends in the surgical management of retroperitoneal sarcoma: An ACS‐NSQIP follow up analysis. Issue 4 (29th July 2019) - Judge, Sean J.; Lata‐Arias, Kathleen; Yanagisawa, Mio; Darrow, Morgan A.; Monjazeb, Arta M.; Kirane, Amanda R.; Bold, Richard J.; Canter, Robert J.; Canter, Daniel J.
Abstract: Background: Calls for multivisceral resection (MVR) of retroperitoneal sarcoma (RPS) are increasing, although the risks and benefits remain controversial. We sought to analyze current 30‐day morbidity and mortality rates, and trends in utilization of MVR in a national database. Methods: Overall morbidity, severe morbidity, mortality rates, and temporal trends were analyzed utilizing the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP). Results: From 2012 to 2015, a total of 564 patients underwent RPS resection with 233 patients (41%) undergoing MVR. The MVR group had a higher rate of preoperative weight loss and larger tumors overall. When comparing MVR to non‐MVR, there was no significant difference in overall morbidity (22% vs 17%, P  = .13), severe morbidity (11% vs 8%, P  = .18), or mortality (<1% vs 2%, P  = .25). On multivariate analysis, MVR was not associated with increased overall morbidity or severe morbidity. Mortality rates were too low for meaningful statistical analysis. Annual rates of MVR ranged from 37% to 46% with no significant change over time ( P  = .47). Results: Short‐term morbidity and mortality rates after MVR for RPS remain acceptable, but rates of MVR show little change over time in NSQIP hospitals. Concerns about increased morbidity and mortality should not be viewed as a contraindication to wider implementation of MVR for RPS.